1998
DOI: 10.1063/1.367189
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial intermixing and arsenic incorporation in thin InP barriers embedded in In0.53Ga0.47As

Abstract: In 0.53 Ga 0.47 As/InP/In 0.53 Ga 0.47 As heterostructures with InP barrier widths between 2 and 20 nm, grown by metal–organic chemical-vapor deposition (MOCVD), were analyzed with respect to interfacial intermixing and As incorporation in the InP. Raman scattering in conjunction with spectroscopic ellipsometry revealed the formation of intermixed (InGa)(AsP) interface layers with a width of about 2 nm. A second effect to be distinguished from interfacial intermixing was detected by the same experimental techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…It is difficult to achieve abrupt interfaces in these structures because both group-III and group-V elements must be switched at the interface. 5 Others, citing Raman data, 6,7 have reported evidence of P incorporation into the InGaAs lattice at growth or anneal temperatures above 640°C. Along with minimizing chamber memory effects, this allows the new group-V element time to diffuse into the existing epilayer, possibly resulting in interfacial broadening.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to achieve abrupt interfaces in these structures because both group-III and group-V elements must be switched at the interface. 5 Others, citing Raman data, 6,7 have reported evidence of P incorporation into the InGaAs lattice at growth or anneal temperatures above 640°C. Along with minimizing chamber memory effects, this allows the new group-V element time to diffuse into the existing epilayer, possibly resulting in interfacial broadening.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] This has been reported in the InAs 1−x P x /In 0.53 Ga 0.47 As 1−y P y system where experimentally measured changes in band lineup are attributed to compositional changes and strain development at the heterointerface. Several authors have reported compressively strained InAsP layers or islands at the InGaAs-on-InP interface.…”
Section: Discussionmentioning
confidence: 88%
“…Similar to the As carry-over effect in MOCVD-grown InP/InGaAs heterostructures, 22,23) the unintentional Ga incorporation is likely due to the sublimation from GaN deposits on the reactor chamber walls and the susceptor which formed during GaN growth pior to InAlN growth. Once the TMGa injection was stopped and the temperature ramped down to the growth temperature of the InAlN layer, Ga species desorbed from the GaN-covered areas and incorporated into the nominally Ga-free layers such as AlN and InAN.…”
Section: Resultsmentioning
confidence: 97%